2021
DOI: 10.1038/s41467-021-26911-7
|View full text |Cite
|
Sign up to set email alerts
|

Overactivated transport in the localized phase of the superconductor-insulator transition

Abstract: Beyond a critical disorder, two-dimensional (2D) superconductors become insulating. In this Superconductor-Insulator Transition (SIT), the nature of the insulator is still controversial. Here, we present an extensive experimental study on insulating NbxSi1−x close to the SIT, as well as corresponding numerical simulations of the electrical conductivity. At low temperatures, we show that electronic transport is activated and dominated by charging energies. The sample thickness variation results in a large sprea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…This state of matter is known as a superinsulator, and was first predicted in [17] (for a review, see [35]). Superinsulators [17,[36][37][38][39], with their divergent electrical resistance, have been experimentally detected in InO [40], TiN [36], NbTiN [41], and NbSi [42]. A recent measurement of the dynamic response of superinsulators confirmed that the potential holding together ± charges is indeed linear [43].…”
Section: Adding Quantum Phase Slipsmentioning
confidence: 97%
“…This state of matter is known as a superinsulator, and was first predicted in [17] (for a review, see [35]). Superinsulators [17,[36][37][38][39], with their divergent electrical resistance, have been experimentally detected in InO [40], TiN [36], NbTiN [41], and NbSi [42]. A recent measurement of the dynamic response of superinsulators confirmed that the potential holding together ± charges is indeed linear [43].…”
Section: Adding Quantum Phase Slipsmentioning
confidence: 97%